Digital Theocracy Strategy In The 2024 Presidential Election Campaign: Its Influence On Public Opinion And Voter Choice - Sahlan, Mukhammad (Eduvest - Journal of Universal Studies, 2023)
Digital technology and social media development have significantly impacted various aspects of life, including politics. Digital campaign strategies have become increasingly important in presidential elections to influence public opinion and voters' choices. In addition, the emergence of the digital theocracy that combines elements of religion and technology in political campaigns adds a new dimension to the modern political arena. This study investigates how digital theocracy strategies used in the 2024 presidential campaign influence public opinion and voter choice. The research method used in this study is a qualitative research method with a content analysis approach. Data will be collected through content observation on various social media and literature studies obtained through Google Scholar. The data that has been collected will be analyzed using a content analysis approach. The results show that the digital theocracy strategy in the presidential election campaign can take various forms, such as sharing religious quotes, participating in religious activities, providing moral messages and religious ethics, religion-based campaigns, responding to religion-based issues, and collaborating with religious figures.